Management and utilization of Green Sea Urchin (Strongylocentrotus droebachiensis) in Eyjafjörður, Northern Iceland - Halldór Pétur Ásbjörnsson (2011)
In this thesis the feasibility of harvesting green sea urchin (Strongylocentrotus droebachiensis) in Eyjafjörður fjord, north Iceland is explored. Fishing methods, regulations, processing and markets area are reviewed from various sources, including interviews with people that participated in sea urchin fisheries around Iceland in the 1990´s. Sea urchins were sampled in Eyjafjörður by the author over a two year period, primarily to investigate the size, gonad yield, gonad colour and density. Three research areas were sampled, split into three different sites (in kelp, along kelp, out of kelp). Results show that the gonad yield was highest in mid to late winter and spawning started in April. The market demands gonad yield of at least 10% and this did occur only for a small part of the year. There was little difference between areas, but the gonad yield in 2010 was considerably lower than in 2009 and spawning did occur earlier. Result for gonad colour shows that 46% end up in first class, the smallest sea urchins had the best colour quality. The value of sea urchin roe is around $40/kg and by far the largest market is in Japan. The second largest market is in France. However, the high quality markets are demanding and the processing is labour intensive. Based on this, harvesting sea urchins in Eyjafjörður is not feasible at this point because of low gonad yield, poor regulation to protect the pioneers and high processing cost. It is suggested that by reducing the number of sea urchins in Eyjafjörður, allowing the kelp forest to grow larger the quality of the sea urchins would increase, but this is not feasible if proper regulations about harvesting are not in place. Verkefnasjóður Sjávarútvegsins